A Preliminary Clinical Observation on Breast Implants and Sarcopenia with Fat Degeneration of the Pectoralis Major Muscle - Kotti, Bouraoui (New Frontiers in Medicine and Medical Research Vol. 9, 2021)
Introduction: Breast augmentation with implants is one of the most performed procedures in plastic surgery all over the world. Despite its popularity, this procedure counts many complications that may require a revision, a replacement or a deposit of the implants. Aims: This study describe a new complication inherited to breast implants and through his observation, wonders about an ethiopathogeny relationship that may be nested with some fat degeneration problems and sarcopenia in the human body. Methods: The author made a clinical observation while replacing implants with capsular contracture noticing a thinning of the pectoralis major muscle and an embrittlement of its fibers with discoloration and yellowness of its corpus. Histopathology specimen were analyzed, photographed and data was collected and discussed. Results: Biopsies were performed on the pectoralis major muscle proving the fatty degeneration and corroborant the atrophy and the sarcopenia. The most common-sense reason was, according to the author, the implant weight and the mechanical pressure on the fibers that led to a cellular stress and a distortion in the regenerative process of the aggressed tissue. Conclusion: A new complication related to breast implants was described. The author request more research to consider an eventual extrapolation of this theory to explain the ethiopathogeny of some classical fatty degeneration processes and sarcopenia observed in different tissues of the human body.